Amphibians and reptiles from two localities in the northern Andes of Colombia (2017)
ABSTRACT: The northern Andes are a geographically, climatically, and ecologically complex area that harbors a high number of species and presents a high level of endemism. However, the landscape of this region has been highly transformed by human activities, including agriculture, cattle grazing, urbanization, and recently, the construction of large infrastructure projects. This study presents a list of amphibians and reptiles compiled from field surveys carried out between 2006 and 2016 in the protected areas surrounding 2 hydroelectric projects located on the eastern flank of the northern Cordillera Central in Colombia. The checklist is comprised of 101 species (43 amphibians and 58 reptiles), including 17 endemic to Colombia and 4 threatened species. The high species density, high representativeness of the regional biodiversity, and high level of amphibian endemism make these 2 protected areas important for conservation of the regional herpetofauna.